A Novel Networked Predictive Control Method for Systems with Random Communication Constraints - Pang, Zhonghua; Bai, Chuandong; Liu, Guoping; Han, Qinglong; Zhang, Xianming (Journal of systems science and complexity, 2021)
This paper presents a novel observer-based predictive control method for networked systems where random network-induced delays, packet disorders and packet dropouts in both feedback and forward channels are considered. The proposed method has three significant features: i) A concept of destination-based lumped (DBL) delay is introduced to represent the combined effects of random communication constraints in each channel; ii) in view of different natures of the random DBL delays in the feedback and forward channels, different compensation schemes are designed; and iii) it is actual control inputs rather than predicted ones that are employed to generate future control signals based on the latest system state estimate available in the controller. For the resulting closed-loop system, a necessary and sufficient stability condition is derived, which is less conservative and also independent of random communication constraints in both channels. Simulation results are provided to demonstrate the effectiveness of the proposed method.